Biblio-information education in the Russian Far East: from traditions to innovations - E. U. Kachanova (Высшее образование в России)
The article shows the history of library education in the Russian Far East on the example of foundation and development of the Department of bibliography and biblio-information activity at Khabarovsk State Institute of Arts and Culture. Special attention is paid to scientific, educational, methodical, and career-guidance activities.